Preventing Child Marriage: Advocating for Marriage Age Education to Foster Family and National Resilience - Latifiani, Dian; Widyawati, Anis; Sumartono, Nike Natasya Dewi; Sani, Rahmawati Melati; Fuad, Choirul; Akbar, Sulthan Faiz; Mubarak, Kareem (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement), 2022)
Children are the buds of the nation's hope that have rights and protection as mandated by the Law of the Republic of Indonesia Number 23 of 2004 concerning the Elimination of Domestic Violence so that they are free from various threats or treatment that degrades human dignity. Other regulations that support child protection are regarding the age limit for marriage as stipulated in Article 7 of the Law of the Republic of Indonesia Number 16 of 2019 concerning Amendments to the Marriage Law No. 1 of 1974, which is 19 years old. However, the empirical reality shows that the target community, namely Fatayat, does not fully understand the urgency that the minimum age of marriage is 19 years. This research is a community service program funded by Semarang State University in Fatayar, South Semarang District, Semarang City. This paper aims to provide an increased understanding of the age of marriage in order to build family resilience in Fatayat, South Semarang District, Semarang City. The results of the study of 11 participants showed a tendency to increase understanding. This research includes several important stages, namely analysis of partner problems, science and technology needs for the community, coordination with partners, outreach and evaluation.